2001
DOI: 10.1097/00000658-200111000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Late Follow-Up of Polypoid Lesions of the Gallbladder Smaller Than 10 mm

Abstract: ObjectiveTo determine the variation in number, size, and symptoms in patients with polypoid lesions of the gallbladder. Summary Background DataA polypoid lesion is any elevated lesion of the gallbladder mucosa. Several studies have been reported in patients undergoing cholecystectomy, but little information exits regarding the natural history of these lesions in nonoperated patients. MethodsA total of 111 patients with ultrasound diagnosis of polypoid lesions smaller than 10 mm were followed up by clinical eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
4
18

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 28 publications
(22 reference statements)
4
80
4
18
Order By: Relevance
“…The detection rate for these lesions has increased with the widespread use of USG in recent years, but it is difficult to define the biologic nature of them radiologically (18). it is suggested that sessile polyps, those are echopenic at USG, with a diameter of greater than 10 mm (2,17,19,20) and associated with gallstones (17,21) are highly suspicious for malignancy and should be removed, whereas asymptomatic patients with polyps smaller than 10 mm are subject to follow-up (20). However, roa et al (3) reported two adenomas less than 5 mm in length and associated with adenocarcinoma in their series and claimed that polyp size criteria to decide on surgical intervention may be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…The detection rate for these lesions has increased with the widespread use of USG in recent years, but it is difficult to define the biologic nature of them radiologically (18). it is suggested that sessile polyps, those are echopenic at USG, with a diameter of greater than 10 mm (2,17,19,20) and associated with gallstones (17,21) are highly suspicious for malignancy and should be removed, whereas asymptomatic patients with polyps smaller than 10 mm are subject to follow-up (20). However, roa et al (3) reported two adenomas less than 5 mm in length and associated with adenocarcinoma in their series and claimed that polyp size criteria to decide on surgical intervention may be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…arly 30 cases of gallbladder adenoma in a polyp less than 10 mm of diameter have been reported in the literature (19,20). This is another evidence supporting the necessity for follow-up in these cases.…”
mentioning
confidence: 82%
“…Çalışmamızdaki yalancı pozitiflik oranı %2.8 olarak saptanmış ve bu pozitifliğin duvara impakte olmuş bir taştan kaynaklandığı histopatolojik incelemede ortaya çıkmıştır. Ancak bazı teorilerde, çok ince saplı poliplerin safra akışı sırasında kopup kaybolabildiği de ifade edilmektedir (6,11).…”
Section: Gereç Ve Yöntemlerunclassified
“…'nın (6) yapmış olduğu bir çalışmada ise polibi olan 98 hastanın 6 yıllık takip sürecinde, hastaların %50'sinde polip boyutları sebat ederken %25'inde boyutlarda artma saptanmıştır. Boyutlarında artma saptanan hastalardan sadece bir tanesinde adenomatöz polip saptanmış olup diğerleri ise kolesterol polipi olarak raporlanmıştır (6). Bizim çalışmamızda da sadece bir hastanın histopatolojik inceleme sonucunda adenomatöz polibe rastlanmıştır.…”
Section: Gereç Ve Yöntemlerunclassified
See 1 more Smart Citation